AI-Based Culture Independent Pervasive M-Learning Prototype Using UI Plasticity Design - H. Miraz, Mahdi; Ali, Maaruf; S. Excell, Peter; Khan, Sajid (Computers, materials & continua, 2021)
This paper explains the development of a culturally inclusive ubiquitous M-Learning platform (“Mobile Academy”) with an AI-based adaptive user interface. The rationale and need for this research and development are justified by the continuing widespread adoption of the Internet and Internet enabled devices, especially smartphones. The M-learning platform was designed from the onset for the global traveller. The characteristics and limitations of the application are also discussed. The Mobile Academy, proof of concept prototype, was created to facilitate teaching and learning on the move or in environments where the use of a desktop computer is inconvenient or simply impossible. The platform’s primary objective was cross-cultural usability through the use of a combination of AI and plasticity of user interface design techniques. The usability evaluation plan was comprehensive and the results obtained were studied in detail. This also included consideration of the results of the SVM (Support Vector Machine) classifiers’ performance and cross-device evaluation. The AI-based adaptive interface prototype has been tested and evaluated to show its merits and capabilities in terms of its usability, inclusivity and effectiveness of the interface. From the results, it was concluded that such a culture independent application was also affordable.